IMPLEMENTASI RELAKSASI AUTOGENIK DAN EDUKASI DIET GUNA PENGENDALIAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI KELURAHAN MERSI PURWOKERTO TIMUR - Dwi Novitasari; Ikit Netra Wirakhmi (Universitas Jenderal Soedirman, 2020)
Hypertension is the number one cause of death in 2030 (WHO, 2014). Hypertension as a silent killer endangers sufferers due to complications such as stroke and acute coronary syndrome. Stress management with relaxation reduce their blood pressure. Other hypertension management is a diet. Education is a promotive, preventive and rehabilitative action. The study of 5 members of the Hypertension Care Group in Mersi was only 1 (20%) people who routinely used relaxation techniques. 2 (40%) people do not consume low-fat milk, 4 (80%) people do not consume celery, 1 (20%) people do not consume cucumber and green tea. The purpose of community service (CS) was to improve control of hypertension by increasing knowledge about the diet of hypertension and autogenic relaxation. The method was carried out by lectures, discussions, question and answer, interviews, demonstrations, and watching videos. The CS target audience was members of group in Mersi, especially RT 05 / RW 01. The implementation of autogenic education and diet education training has 4th sessions. The majority of age are 12 (60%). The majority gender are female 16 (80%). There were 13 (65%) exercise routines, 18 (90%) did not smoke, and there were 18 hypertension offspring (90%). A total of 11 (55.0%) participants have a good diet. Participants have grade 2 hypertension before CS and including grade 1 hypertension after CS showed that there were significant differences between systolic and diastolic blood pressure before and after the activity. Trainees can understand the diet of hypertensive patients and can demonstration autogenic relaxation.